2018
DOI: 10.37358/rc.18.1.6080
|View full text |Cite
|
Sign up to set email alerts
|

Antibioresistance of Microbial Strains Implicated in the Etiology of Sepsis with Oro-Maxillofacial Portal of Entry

Abstract: Methicillin-resistance phenomenon regarding Staphylococcus aureus which is often met as etiologic agent of severe systemic infections with oral-maxillofacial portal of entry imposes the first-line therapeutic schemes readjustment in patients with significant risk factors. Minimum inhibitory concentration (MIC) determination for every isolated S.aureus strain is useful for the antibiotherapy guiding, in order to choose the appropriate antimicrobial substances and to avoid the selection of resistant mutants. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…Although there were significant decreases of the mean percentages for fluoroquinolone resistance, aminoglycoside resistance and carbapenem resistance during the period 2013 to 2016 [34], our study found more than half of the Pseudomonas strains resistant to carbapenems and fluoroquinolones, outcomes consistent with other findings [3,[40][41][42][43].…”
Section: Resultssupporting
confidence: 92%
“…Although there were significant decreases of the mean percentages for fluoroquinolone resistance, aminoglycoside resistance and carbapenem resistance during the period 2013 to 2016 [34], our study found more than half of the Pseudomonas strains resistant to carbapenems and fluoroquinolones, outcomes consistent with other findings [3,[40][41][42][43].…”
Section: Resultssupporting
confidence: 92%
“…Normally, during ribonucleic acid (RNA) translation the amino acids are transferred from an aminoacyl-transfer RNA complex held in the P site of the ribosomal complex to the ones located in the A site, which contributes to the movement of the aminoacyl-transfer RNA complex in site E, and consequently exiting of the ribosome (Figure 2 A) [12,19,20]. Linezolid binds to nucleic acid residues in the peptidyl transferase from site A of the ribosome and prevents the amino acid transfer from aminoacyl groups on transfer RNA located in the P site to the one from the site A, and interrupts the protein elongation (Figure 2 B) [12,17,[19][20][21]. as clindamycin, erythromycin) for long periods of time [22,23].…”
Section: Figure 1 Mechanisms Of Action For the Most Frequently Used mentioning
confidence: 99%
“…The studies developed in the last decades showed an increase in drug resistance in waterborne pathogens against the commonly used antibiotics for the treatment of enteric diseases including tetracycline, erythromycin, ampicillin and cotrimoxazole [10]. Furthermore, resistance to third generation cephalosporins and aztreonam has progressively increased in Romania after their introduction in therapy and over a 10-year interval, the percentage of isolates resistant to ceftazidime has doubled [11].…”
mentioning
confidence: 99%